Managed pressure drilling - Rehm, Bill, 1929- (Gulf Pub., 2008)
With extraction out of depleted wells more important than ever, this new and developing technology is literally changing drilling engineering for future generations. Never before published in book form, these cutting-edge technologies and the processes that surround them are explained in easy-tounderstand language, complete with worked examples, problems and solutions. This volume is invaluable as a textbook for both the engineering student and the veteran engineer who needs to keep up with changing technology.
Keywords: Managed pressure drilling (Petroleum engineering); elektronické knihy; electronic books